Interpretive materials for the flint hills discovery center - Hasler, Fred (Kansas State University, 2011)
In 2004 the City of Manhattan created the entity we now call the Flint Hills Discovery Center (FHDC). Funding was established in 2006 via $50 million in STAR bonds. The center is part of the South End Redevelopment and is currently under construction just south of the Manhattan downtown area. The emphasis of the center is to present information about the Flint Hills and surrounding areas. Because of this focus, it has also been deemed necessary to us the building as an example of “green” design. The design team is pursuing a gold certification from the U.S. Green Building Council (USGBC), via the LEED Green Building Rating System. Credits that are proposed cover all 7 major topics of the rating system. In fact, one of the Innovation and Design credits proposed involves sustainable design education programs and displays inside the building. Fred Hasler, P.E., LEED AP, with the support of members from the USGBC Student Chapter is currently developing ideas, concepts and materials for the educational programs and interpretive displays proposed. These focus on what the LEED Rating System is, how the building uses its systems and materials to be “green” and finally what can visitors of the center take home and apply in their daily lives to lessen our consumption of resources and the strain on our environment. Static and dynamic displays are planned in order to engage visitors of all ages and get them excited about all the things they can do personally to make a difference. The creation of the FHDC offers a great opportunity for the center staff and faculty/students of K-State to build a relationship that can last for many years. It is critical for students to gain knowledge about the process of sustainable design and this project gives them a hands-on opportunity that is difficult to duplicate in the classroom. Students will have an opportunity to develop interdisciplinary relationships between themselves, K-State faculty, the building design team and the FHDC staff. This initial program is allowing students to use their creativity to teach others about what they have learned as well as define a framework for future work at the FHDC. In conclusion, all parties benefit from this program. The FHDC is gaining an insight/point of view from a constituency they are targeting; Faculty at K-State are providing an educational service to the community; Students are able to learn practical skills related to sustainable design practices; Visitors to the center learn intimately what is involved in the sustainable design of buildings and how they can apply that knowledge at home or their workplace.